Understanding Dutertismo: Populism and Democratic Politics in the Philippines - Parcon, Ian Clark R (Archīum Ateneo, 2021)
The present study investigates how the normative views on democracy influence the analysis of Dutertismo. There are two prevailing normative views that is operative in the analysis of democracy which also provide differing take on the role of populism. On the one hand, the deliberative perspective emphasizes on consensus building and considers populism as irreconcilable with its democratic framework. On the other hand, the agonistic model privileges conflict and tension and considers populism as an essential component of democracy. I shall advance the thesis that a third perspective is necessary which considers the framework of mutual correction where democracy is seen as a postponed synthesis between the task of consensus building and the recognition of irreducible conflict. It is through this framework that the complexity of democracy in the Philippines can be comprehensively grasped and the role of populism be extensively understood.